Community attitudes towards environmental tobacco smoke in licensed premises: follow‐up study after the Sharp case - Flora Tzelepis; Raoul A. Walsh; Christine L. Paul (Elsevier, 2003)
Abstract Objective: To examine community attitudes towards environmental tobacco smoke in licensed premises after the Sharp case decision. Method: 723 randomly selected New South Wales residents aged 18 years and over completed a telephone survey in November 2001. Results: The vast majority supported some form of smoking restriction in licensed clubs (92.1%) and hotels (90.0%). Compared with a 2000 survey, respondents in the 2001 survey were significantly more likely to support a total smoking ban in licensed clubs and hotels. When support was assessed using a ban‐only question, 66.8% supported banning smoking in pubs/clubs. Approximately half reported being less likely to visit non‐eating areas of licensed clubs (51.2%) and hotels (49.8%) if smoking were permitted and these proportions were significantly higher than in the 2000 survey. A majority (83.1%) thought bar workers' health should be a major consideration when deciding how to handle smoking in pubs/clubs. More than half (56.8%) believed pubs/clubs would experience significant financial problems if smoking bans were introduced. Conclusions and implications: In New South Wales, majority support exists for banning smoking in pubs and clubs. Legislation banning smoking in all indoor drinking and gaming areas should be introduced immediately.